Pengaruh Solidaritas Sosial Terhadap Resiliensi Buruh ditengah Pandemi Covid-19 - Versanudin Hekmatyar; Nike Vonika (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
The objective of this study is to to show the effect of social solidarity on labor resilience in the midst of the Covid-19 pandemic. By using quantitative approach, data was collected and presented descriptively, as well hypothesis test. Labor with strong social solidarity is expected to have resilience in the face of the Covid-19 pandemic. The results showed that social solidarity had a significant effect on labor resilience in the midst of the Covid-19 pandemic. Social solidarity exists as an effort from the community to minimize the impact of the Covid-19 pandemic so that it can return to its original state. The extreme instability amid the Covid-19 pandemic has forced communities to make concessions to one another and share responsibility for surviving and recovering from the covid-19 pandemic.